Communication Functions in Speech Act Tolerance in The Multiethnic Community Interaction in East Java As A Representation of Ecological Establishment in East Java - Arief Rijadi (Pancaran Pendidikan, 2018)
One important aspect of communication is tolerance. In the 18th century, tolerance was an important value that was exalted, besides the value of truth and humanism. Tolerance is a basic and fundamental quality in social relations that rejects violence and coercion. In this case, tolerant in speech becomes urgent to build ideal communication in diverse communities. In the reality of social interaction, tolerance is expressed through speeches chosen by the participants. These tolerant speeches have communication functions. This study aims to describe the communication functions of tolerant speech acts expressed in the communication of East Java Javanese multiethnic communities. This research was conducted using a pragmatic approach and ethnographic research design communication. Data were collected in the form of speech units and speech contexts that occurred in East Javanese multiethnic speeches. Selected data were analyzed by descriptive techniques including the stages of identification and classification, interpretation, pairing, and meaning of data. The results of the study were directed at describing the diversity of communication functions of tolerant speech acts including among others (1) the function of harmony, (2) the function of familiarity, (3) function of forgiveness, (4) function of honesty, and (5) honorific function.